2015
DOI: 10.1103/physrevlett.115.131603
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing Chaos Using Four-Point Functions in Two-Dimensional Conformal Field Theory

Abstract: We study chaotic dynamics in two-dimensional conformal field theory through out-of-time-order thermal correlators of the form hWðtÞVWðtÞVi. We reproduce holographic calculations similar to those of Shenker and Stanford, by studying the large c Virasoro identity conformal block. The contribution of this block to the above correlation function begins to decrease exponentially after a delay of ∼t à − ðβ=2πÞ log β 2 E w E v , where t à is the fast scrambling time ðβ=2πÞ log c and E w ; E v are the energy scales of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
387
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 389 publications
(401 citation statements)
references
References 25 publications
13
387
1
Order By: Relevance
“…In the setting of two-dimensional CFT, Roberts and Stanford [31] have shown that large central charge, a large gap for higher-spin Virasoro primary operators, and a "low" density of light states is enough to guarantee a maximal Lyapunov exponent λ L = 2πT . Their argument would go through more or less unaltered for a CQM invariant under a Virasoro symmetry with large central charge, assuming that such a thing existed.…”
Section: Electric Ads2mentioning
confidence: 99%
“…In the setting of two-dimensional CFT, Roberts and Stanford [31] have shown that large central charge, a large gap for higher-spin Virasoro primary operators, and a "low" density of light states is enough to guarantee a maximal Lyapunov exponent λ L = 2πT . Their argument would go through more or less unaltered for a CQM invariant under a Virasoro symmetry with large central charge, assuming that such a thing existed.…”
Section: Electric Ads2mentioning
confidence: 99%
“…A particularly interesting type of four-point function is the out-of-time-order correlation function (OTOC) F (t) = χ j (t)χ k (0)χ j (t)χ k (0) , which has been proposed as a measure of chaos in quantum systems [15][16][17][18][19][20] (see refs. [21][22][23][24] for experimental proposals for measuring OTOC).…”
Section: Jhep05(2017)125mentioning
confidence: 99%
“…evolution of entanglement entropy in excited states created by local operators [13][14][15]; the issue of universality in 2d conformal field theories [16,17]; entanglement entropy in higher spin theories [18]; and the emergence of chaos in thermal systems [19].…”
Section: Jhep07(2015)131mentioning
confidence: 99%